Epigenetic Dysregulation in Laryngeal Squamous Cell Carcinoma - Wong, Thian-Sze (Hindawi Publishing Corporation, 2012)
Laryngeal carcinoma is a common head and neck cancer with poor prognosis. Patients with laryngeal carcinoma usually present late leading to the reduced treatment efficacy and high rate of recurrence. Despite the advance in the use of molecular markers for monitoring human cancers in the past decades, there are still no reliable markers for use to screen laryngeal carcinoma and follow the patients after treatment. Epigenetics emerged as an important field in understanding the biology of the human malignancies. Epigenetic alterations refer to the dysregulation of gene, which do not involve the alterations of the DNA sequence. Major epigenetic changes including methylation imbalance, histone modification, and small RNA dysregulation could play a role in the development of human malignancies. Global epigenetic change is now regarded as a molecular signature of cancer. The characteristics and behavior of a cancer could be predicted based on the specific epigenetic pattern. We here provide a review on the understanding of epigenetic dysregulation in laryngeal carcinoma. Further knowledge on the initiation and progression of laryngeal carcinoma at epigenetic level could promote the translation of the knowledge to clinical use.